Heterodimers of photoreceptor-specific nuclear receptor (PNR/NR2E3) and peroxisome proliferator-activated receptor (PPARγ) are disrupted by retinal disease-associated mutations - Fulton, Joel; Mazumder, Bismoy; Whitchurch, Jonathan; Monteiro, Cintia J.; Collins, Hilary M.; Chan, Chun M.; Clemente, Maria P.; Hernandez Quiles, Miguel; Stewart, Elizabeth A.; Amoaku, Winfried; Moran, Paula M.; Mongan, Nigel P.; et al. (Nature Publishing Group, 2017)
Photoreceptor-specific nuclear receptor (PNR/NR2E3) and Tailless homolog (TLX/NR2E1) are human orthologs of the NR2E group, a subgroup of phylogenetically related members of the Nuclear Receptor (NR) superfamily of transcription factors. We assessed the ability of these NRs to form heterodimers with other members of the human NRs representing all major subgroups. The TLX ligand binding domain (LBD) did not appear to form homodimers or interact directly with any other NR tested. The PNR LBD was able to form homodimers, but also exhibited robust interactions with the LBDs of PPARγ/NR1C3 and TRβ/NR1A2. The binding of PNR to PPARγ was specific for this paralog, as no interaction was observed with the LBDs of PPARαNR1C1 or PPARδNR1C2. In support of these findings, PPARγ and PNR were found to be co-expressed in human retinal tissue extracts and could be co-immunoprecipitated as a native complex. Selected sequence variants in the PNR LBD associated with human retinopathies, or a mutation in the dimerization region of PPARγ LBD associated with familial partial lipodystrophy type 3, were found to disrupt PNR/PPARγ complex formation. Wild type PNR, but not a PNR309G mutant, was able to repress PPARγ-mediated transcription in reporter assays. In summary our results reveal novel heterodimer interactions in the NR superfamily, suggesting previously unknown functional interactions of PNR with PPARγ and TRβ that have potential importance in retinal development and disease.